Geotechnologies applied in the analysis of urban growth in the Immediate Region of the city of Araripina-PE - Paiva, Anderson Luiz Ribeiro de (2024)
Urban expansion is a phenomenon that involves an intense anthropogenic modification of the environment, however, these changes can result in negative environmental impacts, such as the replacement of vegetated areas and the sealing of the soil. This study aims to detect the changes that occurred in the Immediate Region of Araripina as a result of urban expansion and of the spatial changes which have taken place in all of its region. Using the Google Earth Engine cloud processing platform and the JavaScript programming language, georeferenced images of the study area were obtained from the database of the TM Landsat 5 and OLI Landsat 8 satellites, referring to the years 1992 and 2021, respectively. The biophysical parameters, Normalized Difference Built-Up Index (NDBI), Normalized Difference Vegetation Index (NDVI) and Built-Up, and land use and occupation were then calculated. The results showed that there was an increase in the value of NDBI and Built-Up in 2021, compared to 1992, as a consequence of changes in land use and occupation, and also of the expansion of built areas in the region. The results of the biophysical indices were consistent with the land use and occupation data obtained by the MapBiomas project, showing that the urban area land use class suffered a significant increase over the years, indicating, therefore, the expansion of the region’s urban centers. The technique used therefore proved to be suitable for use by public managers, being quick and efficient, in defining plans and actions that involve the urbanization process.